2020
DOI: 10.31224/osf.io/yxb5u
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plastic waste reprocessing for circular economy: A systematic review of risks to occupational and public health from legacy substances and extrusion

Abstract: Increasing aspirations to develop a circular economy for waste plastics will result in an expansion of the global plastics reprocessing sector over the coming decades. Here we focus on two critical challenges within the value chain that as a result of such increased circularity may exacerbate existing issues for occupational and public health (1): Legacy contamination in secondary plastics, addressing the risk of materials and substances being inherited from the previous use and carried through into new produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…The present review is part of a wider piece of research that investigated the risks to human health and safety from the mismanagement of plastic waste. While this paper presents findings on the risks to human health from the open, uncontrolled burning, another paper by Cook et al presents on plastics extrusion and legacy substance contamination in secondary plastics. The same initial pool of literature was used in the preparation of the two reviews as detailed in Section S.1.4, obtained by the same PRISMA adapted method, presented in Cook et al…”
Section: Methodsmentioning
confidence: 99%
“…The present review is part of a wider piece of research that investigated the risks to human health and safety from the mismanagement of plastic waste. While this paper presents findings on the risks to human health from the open, uncontrolled burning, another paper by Cook et al presents on plastics extrusion and legacy substance contamination in secondary plastics. The same initial pool of literature was used in the preparation of the two reviews as detailed in Section S.1.4, obtained by the same PRISMA adapted method, presented in Cook et al…”
Section: Methodsmentioning
confidence: 99%
“…Emissions from extrusion of the main conventional plastics used in packaging, such as polypropylene (PP), PE, PET, high density polyethylene and low density polyethylene (LDPE) are not thought to result in harm to human health if carried out at controlled temperatures and using relatively pure In the Global South, ventilation may not always be provided in plastics extrusion facilities. For example, a review by Cook et al (2020b) found examples of facilities investigated in China where only passive ventilation was provided as a control measure. Other examples were identified in the multimedia evidence presented in Table 4, where workers were in close proximity to extruders without any observable mechanical ventilation or personal protective equipment.…”
Section: Emissions To Airmentioning
confidence: 99%
“…Although the most common polyolefins and PET do not usually result in harmful emissions if ventilation is sufficiently controlled, there some is evidence that if materials are not sourced or sorted carefully then they may be inadvertently mixed with plastics such as polystyrene and PVC, both of which result in harmful emissions when extruded (Cook et al, 2020b;He et al, 2015). Moreover, if the polyolefins and PET have originated form a source that involves some potentially hazardous substances being added, for example electrical casings, then these substances may volatilise when heated, exposing workers.…”
Section: Emissions To Airmentioning
confidence: 99%
See 2 more Smart Citations